The Usability Analysis Online Learning Site for Supporting Computer programming Course Using System Usability Scale (SUS) in a University - Derisma, Derisma (International journal of interactive mobile technologies, 2020)
Computer programming subject is the most-feared subject by students because it is hard to learn. At present, various learning media for programming are available, therefore, the learning process which was often considered as boring and hard to learn becomes interesting and easy to do. One of those media is through internet. This condition is parallel with various number of learning-based online sites that currently grow, including CodeSaya; one of the learning websites for computer programming languages. Usability is an important aspect to be noticed for the users to feel facilitated in using it, acquiring the required knowledge, and be interested to always rely on the site within the learning process. By collecting the user perception about user interfaces, questionnaire might help identifying the weakness in website usability to perform improvements. This research was done to analyze the success of online learning site, whether it meets the usability criteria by implementing System Usability Scale (SUS) questionnaire as the research instrument. SUS is an effective and reliable instrument to measure the usability of various products and services. The research questionnaire consisted of 10 questions which disseminated toward 162 respondents divided into two groups, namely familiar users that amounted to 81 respondents and unfamiliar users that amounted to 81 respondents as well. The usability of CodeSaya site acquired 72.1 of score for familiar users and 70 of score for unfamiliar users. The score acquired from the rating given by familiar respondents only a bit higher compared to the unfamiliar respondents. The rating in alphabet resulted in B or Good. It can be concluded that this computer programming learning site has met the usability criteria, therefore, it can be implemented as a learning medium that is feasible to be used by the users.